Electroplating method of molybdenum-copper material

By performing multi-step electroplating of molybdenum copper material, including bottom nickel plating, flash nickel and nickel plating, combined with specific plating solution composition and process parameters, the poor binding force and easy foaming of the nickel plating layer after electroplating of molybdenum copper material is solved. Problem, high-quality coating formation is achieved, and the performance and service life of the material are improved.

CN119465325AActive Publication Date: 2025-02-18YUYAO ADISHENG ELECTROPLATING TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411701498.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The nickel-plated layer of molybdenum copper material has poor binding force after electroplating, which is prone to foaming, affecting the aesthetics, corrosion resistance and service life of the coating.

Method used

Multi-step electroplating method is adopted, including pretreatment steps such as oil removal, oxidation, pickling, activation, etc., followed by plating nickel, flash nickel and nickel plating in the nickel plating solution, and finally gold plating, using specific plating solution composition and process Parameters to form a high-quality plating layer.

Benefits of technology

It significantly improves the bonding force and density of the nickel-plated layer, reduces bubble phenomenon, enhances the gloss and corrosion resistance of the coating, and improves the overall performance of molybdenum copper material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153418820000141
    Figure BDA0005153418820000141
  • Figure BDA0005153418820000151
    Figure BDA0005153418820000151
Patent Text Reader

Abstract

The invention relates to the technical field of metal electroplating, and particularly discloses an electroplating method of a molybdenum-copper material. The electroplating method for the molybdenum-copper material comprises the following steps that S1, the molybdenum-copper material is sequentially subjected to oil removal, water washing, oxidation, water washing, acid pickling, water washing, activation and water washing treatment, and a pretreated molybdenum-copper material is obtained; s2, the pretreated molybdenum-copper material is immersed in a nickel plating solution for bottom nickel plating, then immersed in a nickel flashing solution for nickel flashing, finally immersed in the nickel plating solution for nickel plating and washed with water, and a nickel-plated molybdenum-copper material is obtained; s3, the nickel-molybdenum-copper plated material is immersed in a gold plating solution for gold plating and water washing, and a gold-plated nickel-molybdenum-copper material is obtained; the nickel plating solution comprises nickel salt, boric acid, a deep eutectic solvent, chitosan-based ionic liquid, a brightener and a dispersing agent. The electroplating method is simple in step and low in cost, and the obtained nickel plating layer is high in binding force and smooth and flat in surface and has wide market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal electroplating, and more specifically, to an electroplating method of a molybdenum-copper material. Background Art

[0002] Copper-molybdenum materials, as a high-performance alloy, have been widely used in aerospace, electrical and electronic, and mechanical manufacturing due to their excellent electrical and thermal conductivity, high strength, and high hardness. During the electroplating process, the bonding force between the coating and the base material is a key factor in ensuring the quality and performance of the coating. However, copper-molybdenum materials have high surface hardness and stable chemical properties, and are not easy to react with metal ions in the electroplating solution, making it difficult for the coating to form a strong bond on the surface of the material. In addition, the thermal expansion coefficient of copper-molybdenum materials is significantly different from that of commonly used electroplated metals, which also increases the risk of stress and blistering in the coating during heat treatment or use.

[0003] At present, CN118773690A discloses a nickel plating method for a copper-molybdenum-copper layered composite material, comprising the following steps: 1) pretreatment: pretreatment of copper-molybdenum-copper composite material parts in a chain furnace under a hydrogen atmosphere to reduce the interfacial stress of the parts and remove organic impurities; 2) degreasing: immersing the copper-molybdenum-copper composite material parts in a degreasing solution to remove oil stains and fingerprints on the surface of the parts; 3) etching: immersing the copper-molybdenum-copper composite material parts in an etching solution and shaking them quickly to remove the oxide scale and poor surface structure on the surface of the parts; 4) activation: immersing the copper-molybdenum-copper composite material parts in an activation solution to further remove the residual oxide film on the surface of the parts to expose the base metal; 5) pre-nickel plating: a large current impacts nickel to enhance the bonding strength between the nickel layer and the base material; 6) nickel electroplating: using a nickel sulfate system for pulse nickel plating; however, the problems of poor bonding strength and blistering of the nickel plating layer after electroplating have not been completely solved; not only the aesthetics and corrosion resistance of the coating are affected, but also the service life and reliability of the product are reduced. Summary of the invention

[0004] In order to solve the problem that the nickel-plated layer of the existing molybdenum-copper material has poor bonding strength and is prone to blistering after electroplating, the present application provides a method for electroplating a molybdenum-copper material.

[0005] The present application provides a method for electroplating molybdenum-copper materials, which adopts the following technical solution:

[0006] A method for electroplating a molybdenum-copper material comprises the following steps:

[0007] S1. The molybdenum-copper material is sequentially subjected to degreasing, water washing, oxidation, water washing, pickling, water washing, activation, and water washing treatment to obtain a pretreated molybdenum-copper material;

[0008] S2, the pretreated molybdenum-copper material is first immersed in a nickel plating solution for bottom nickel plating, then immersed in a nickel flash solution for nickel flashing, and finally immersed in a nickel plating solution for nickel plating, washed with water, to obtain a nickel-plated molybdenum-copper material;

[0009] S3, immersing the nickel-molybdenum-copper plated material in a gold plating solution for gold plating, and washing with water to obtain a gold-plated nickel-molybdenum-copper material;

[0010] The nickel plating solution comprises the following components in mass concentrations: 80-110 g / L of nickel salt, 40-50 g / L of boric acid, 50-150 mg / L of low eutectic solvent, 30-60 mg / L of chitosan-based ionic liquid, 15-45 mg / L of brightener, 40-80 mg / L of dispersant, 50-70 mg / L of defoamer, 10-50 mg / L of buffer, and the balance is deionized water.

[0011] Preferably, the nickel salt is at least one of nickel chloride, nickel sulfamate, nickel sulfate, nickel carbonate, nickel acetate, nickel formate, and nickel borofluoride.

[0012] Preferably, the low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:2.

[0013] Preferably, the chitosan-based ionic liquid is prepared by the following method:

[0014] Step A, add 1.32 g of N-methylbenzimidazole and 2-2.5 g of dibromopropane to 50 mL of acetone, react at 45-55° C. for 12-24 h, and then remove the solvent by rotary evaporation to obtain an intermediate;

[0015] Step B: add 1.5 g of the intermediate and 0.01-0.05 g of potassium carbonate into 50 mL of distilled water, stir evenly, then add 1.0-1.8 g of chitosan and stir evenly, reflux at 110-120° C. for 18-24 h, cool, filter, wash with ethanol, and dry to obtain a chitosan-based ionic liquid.

[0016] Preferably, the brightener is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine in a mass ratio of 3-7:10.

[0017] Preferably, the dispersant is at least one of polyethylene glycol, Tween, Span, lecithin, and rhamnolipid; and the defoaming agent is an organosilicon defoaming agent.

[0018] Preferably, the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0019] Preferably, the nickel flash solution comprises the following components in mass concentration: 100 g / L nickel sulfate, 30 g / L potassium carbonate, 40 mg / L sodium alginate, 20 mg / L ethylene-acrylic acid copolymer, 10 mg / L carbazole, and the balance is deionized water.

[0020] Preferably, the gold plating solution comprises the following components in mass concentration: 10-20 g / L sodium gold sulfite, 15-30 g / L malic acid, 10-20 g / L phytic acid, 10-40 mg / L sodium polydisulfide propane sulfonate, 10-30 mg / L sorbitol, 20-80 mg / L diethyl dithiophosphate ammonium salt, and the balance is deionized water.

[0021] Preferably, the parameters of the nickel plating in step S2 are: external magnetic field of 0.3-0.4T, temperature of 30-40°C, current density of 4-8A / dm 2 , the pulse frequency is 10Hz, the duty cycle is 20%, and the electroplating is 120-150s; the parameters of the nickel plating are: the external magnetic field is 0.6-0.8T, the temperature is 40-60℃, and the current density is 1-2A / dm 2 , the pulse frequency is 10Hz, the duty cycle is 30%, and the electroplating time is 300-360s.

[0022] In summary, this application has the following beneficial effects:

[0023] 1. In the electroplating process of the present application, the molybdenum-copper material is first subjected to pretreatment operations such as degreasing, oxidation, pickling, activation, etc. in sequence to improve the activity and roughness of the surface of the molybdenum-copper material, thereby enhancing the bonding force between the plated layer and the molybdenum-copper material; then, during nickel plating, base nickel plating, flash nickel plating, and nickel plating are performed. Through three nickel platings, a thin and uniform nickel layer is formed on the surface of the molybdenum-copper material, which well solves the problem of poor bonding force and easy blistering of the nickel plating layer after electroplating, and improves the density and glossiness of the plating layer; finally, gold plating is performed to form a gold layer on the nickel plating layer to improve the conductivity, corrosion resistance and aesthetics of the molybdenum-copper material; the electroplating method of the present invention has simple steps, low cost, is suitable for industrial production, and has a very excellent market prospect.

[0024] 2. The nickel plating solution of the present application includes nickel salt, boric acid, low eutectic solvent, chitosan-based ionic liquid, brightener, dispersant, defoamer, buffer, etc. Nickel salt is used as the main salt to provide divalent nickel ions for the plating solution, ensuring the continuous nickel plating, and is the main source of the chemical composition of the nickel plating layer; salicylic acid and N, N-dimethylurea are used as low eutectic solvents, which can improve the conductivity and electrochemical window of the nickel plating solution, help to obtain a high-quality nickel plating layer, and can reduce the occurrence of side reactions, thereby improving the binding force of the nickel plating layer; chitosan-based ionic liquid is prepared using N-methylbenzimidazole, dibromopropane, and chitosan as raw materials, which can form a complex with nickel ions, promote the deposition of metallic nickel on the surface of copper-molybdenum materials, accelerate the deposition rate, and improve the electroplating efficiency and the quality of the nickel plating layer The amount of dispersant, defoamer and buffer can ensure the uniform distribution of nickel ions in the nickel plating solution and prevent the occurrence of agglomeration, thereby helping to form a uniform and dense nickel plating layer. The various components in the nickel plating solution play a synergistic role and assist each other to jointly improve the performance of the nickel plating solution and the quality of the nickel plating layer. At the same time, the formation of the nickel plating layer is also beneficial to the subsequent gold plating process, effectively improving the overall performance of the overall plating layer.

[0025] 3. The nickel flash solution of the present application includes nickel sulfate, potassium carbonate, sodium alginate, ethylene-acrylic acid copolymer, and carbazole. Carbazole is used as a catalyst to promote the electroplating reaction. The components interact with each other to quickly form a thin and uniform nickel layer on the surface of the molybdenum-copper material. This nickel layer can be used as a subsequent electroplating layer to significantly improve the adhesion between the nickel-plated layer and the molybdenum-copper material. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with preparation examples and embodiments.

[0027] Preparation Example 1

[0028] Chitosan-based ionic liquids are prepared by the following method:

[0029] Step A, add 1.32 g of N-methylbenzimidazole and 2 g of dibromopropane to 50 mL of acetone, react at 45° C. for 24 h, and then remove the solvent by rotary evaporation to obtain an intermediate;

[0030] Step B: add 1.5 g of the intermediate and 0.01 g of potassium carbonate into 50 mL of distilled water, stir evenly, then add 1.0 g of chitosan and stir evenly, reflux at 110° C. for 24 h, cool, filter, wash with ethanol, and dry to obtain a chitosan-based ionic liquid.

[0031] Preparation Example 2

[0032] Chitosan-based ionic liquids are prepared by the following method:

[0033] Step A, add 1.32 g of N-methylbenzimidazole and 2.2 g of dibromopropane to 50 mL of acetone, react at 50° C. for 18 h, and then remove the solvent by rotary evaporation to obtain an intermediate;

[0034] Step B: add 1.5 g of the intermediate and 0.03 g of potassium carbonate into 50 mL of distilled water, stir evenly, then add 1.4 g of chitosan and stir evenly, reflux at 115° C. for 20 h, cool, filter, wash with ethanol, and dry to obtain a chitosan-based ionic liquid.

[0035] Preparation Example 3

[0036] Chitosan-based ionic liquids are prepared by the following method:

[0037] Step A, add 1.32 g of N-methylbenzimidazole and 2.5 g of dibromopropane to 50 mL of acetone, react at 55° C. for 12 h, and then remove the solvent by rotary evaporation to obtain an intermediate;

[0038] Step B: add 1.5 g of the intermediate and 0.05 g of potassium carbonate to 50 mL of distilled water, stir evenly, then add 1.8 g of chitosan and stir evenly, reflux at 120° C. for 18 h, cool, filter, wash with ethanol, and dry to obtain a chitosan-based ionic liquid.

[0039] Preparation Examples 4-6 and Comparative Preparation Examples 1-6 provide a nickel plating solution.

[0040] Preparation Example 4

[0041] The nickel plating solution includes the following components in mass concentration: nickel salt 80 g / L, boric acid 40 g / L, low eutectic solvent 50 mg / L, chitosan-based ionic liquid 30 mg / L, brightener 15 mg / L, dispersant 40 mg / L, defoamer 50 mg / L, buffer 10 mg / L, and the balance is deionized water;

[0042] Among them, the nickel salt is nickel chloride; the low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:2; the chitosan-based ionic liquid is Preparation Example 1; the brightener is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine in a mass ratio of 3:10; the dispersant is polyethylene glycol; the defoamer is silicone defoamer BYK-037; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0043] Preparation Example 5

[0044] The nickel plating solution includes the following components in mass concentrations: 95 g / L nickel salt, 45 g / L boric acid, 100 mg / L deep eutectic solvent, 45 mg / L chitosan-based ionic liquid, 30 mg / L brightener, 60 mg / L dispersant, 60 mg / L defoamer, 30 mg / L buffer, and the balance is deionized water;

[0045] Among them, the nickel salt is nickel sulfate; the low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:2; the chitosan-based ionic liquid is Preparation Example 2; the brightener is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine in a mass ratio of 1:2; the dispersant is Tween 80; the defoamer is silicone defoamer BYK-018; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0046] Preparation Example 6

[0047] The nickel plating solution includes the following components in mass concentration: nickel salt 110 g / L, boric acid 50 g / L, low eutectic solvent 150 mg / L, chitosan-based ionic liquid 60 mg / L, brightener 45 mg / L, dispersant 80 mg / L, defoamer 70 mg / L, buffer 50 mg / L, and the balance is deionized water;

[0048] Among them, the nickel salt is obtained by mixing nickel chloride and nickel acetate in a mass ratio of 1:1; the low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:2; the chitosan-based ionic liquid is Preparation Example 3; the brightener is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine in a mass ratio of 7:10; the dispersant is lecithin; the defoamer is a silicone defoamer BYK-066N; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0049] Comparative Preparation Example 1

[0050] Compared with Preparation Example 1, the only difference from Preparation Example 4 is that no chitosan-based ionic liquid is added, as follows:

[0051] The nickel plating solution includes the following components in mass concentration: nickel salt 80g / L, boric acid 40g / L, low eutectic solvent 50mg / L, brightener 15mg / L, dispersant 40mg / L, defoamer 50mg / L, buffer 10mg / L, and the balance is deionized water;

[0052] Among them, the nickel salt is nickel chloride; the low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:2; the brightener is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine in a mass ratio of 3:10; the dispersant is polyethylene glycol; the defoamer is silicone defoamer BYK-037; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0053] Comparative Preparation Example 2

[0054] Compared with Preparation Example 2, the only difference from Preparation Example 4 is that the chitosan-based ionic liquid is replaced by an equal mass of 1-methylimidazole tetrafluoroborate, as follows:

[0055] The nickel plating solution includes the following components in mass concentration: nickel salt 80 g / L, boric acid 40 g / L, deep eutectic solvent 50 mg / L, 1-methylimidazole tetrafluoroborate 30 mg / L, brightener 15 mg / L, dispersant 40 mg / L, defoamer 50 mg / L, buffer 10 mg / L, and the balance is deionized water;

[0056] Among them, the nickel salt is nickel chloride; the low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:2; the brightener is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine in a mass ratio of 3:10; the dispersant is polyethylene glycol; the defoamer is silicone defoamer BYK-037; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0057] Comparative Preparation Example 3

[0058] Compared with Preparation Example 3, the only difference from Preparation Example 4 is that the chitosan-based ionic liquid is replaced by an equal mass of chitosan, as follows:

[0059] The nickel plating solution includes the following components in mass concentration: nickel salt 80g / L, boric acid 40g / L, low eutectic solvent 50mg / L, chitosan 30mg / L, brightener 15mg / L, dispersant 40mg / L, defoamer 50mg / L, buffer 10mg / L, and the balance is deionized water;

[0060] Among them, the nickel salt is nickel chloride; the low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:2; the brightener is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine in a mass ratio of 3:10; the dispersant is polyethylene glycol; the defoamer is silicone defoamer BYK-037; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0061] Comparative Preparation Example 4

[0062] Compared with Preparation Example 4, the only difference from Preparation Example 4 is that no deep eutectic solvent is added, as follows:

[0063] The nickel plating solution includes the following components in mass concentrations: 80 g / L nickel salt, 40 g / L boric acid, 30 mg / L chitosan-based ionic liquid, 15 mg / L brightener, 40 mg / L dispersant, 50 mg / L defoamer, 10 mg / L buffer, and the balance is deionized water;

[0064] Among them, the nickel salt is nickel chloride; the chitosan-based ionic liquid is the one prepared in Example 1; the brightener is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine in a mass ratio of 3:10; the dispersant is polyethylene glycol; the defoamer is the silicone defoamer BYK-037; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0065] Comparative Preparation Example 5

[0066] Comparative Preparation Example 5 is different from Preparation Example 4 only in that the brightener is only L-alanine benzyl ester p-toluenesulfonate, specifically as follows:

[0067] The nickel plating solution includes the following components in mass concentration: nickel salt 80 g / L, boric acid 40 g / L, low eutectic solvent 50 mg / L, chitosan-based ionic liquid 30 mg / L, brightener 15 mg / L, dispersant 40 mg / L, defoamer 50 mg / L, buffer 10 mg / L, and the balance is deionized water;

[0068] Among them, the nickel salt is nickel chloride; the low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:2; the chitosan-based ionic liquid is Preparation Example 1; the brightener is L-alanine benzyl ester toluenesulfonate; the dispersant is polyethylene glycol; the defoamer is silicone defoamer BYK-037; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0069] Comparative Preparation Example 6

[0070] Comparative Preparation Example 6 is different from Preparation Example 4 only in that the brightener is only N-arylpyridine, as follows:

[0071] The nickel plating solution includes the following components in mass concentration: nickel salt 80 g / L, boric acid 40 g / L, low eutectic solvent 50 mg / L, chitosan-based ionic liquid 30 mg / L, brightener 15 mg / L, dispersant 40 mg / L, defoamer 50 mg / L, buffer 10 mg / L, and the balance is deionized water;

[0072] Among them, the nickel salt is nickel chloride; the low eutectic solvent is obtained by mixing salicylic acid, N, N-dimethylurea and distilled water in a molar ratio of 1:1:2; the chitosan-based ionic liquid is Preparation Example 1; the brightener is only N-arylpyridine; the dispersant is polyethylene glycol; the defoamer is silicone defoamer BYK-037; and the buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:1.

[0073] Preparation Example 7 provides a nickel flash solution.

[0074] Preparation Example 7

[0075] The nickel flash solution includes the following components in mass concentration: 100 g / L nickel sulfate, 30 g / L potassium carbonate, 40 mg / L sodium alginate, 20 mg / L ethylene-acrylic acid copolymer, 10 mg / L carbazole, and the balance is deionized water.

[0076] Preparation Examples 8-10 provide a gold plating solution.

[0077] Preparation Example 8

[0078] The gold plating solution includes the following components in mass concentration: 10 g / L sodium gold sulfite, 15 g / L malic acid, 10 g / L phytic acid, 10 mg / L sodium polydisulfide propane sulfonate, 10 mg / L sorbitol, 20 mg / L diethyl dithiophosphate ammonium salt, and the balance is deionized water.

[0079] Preparation Example 9

[0080] The gold plating solution includes the following components in mass concentration: 15 g / L sodium gold sulfite, 25 g / L malic acid, 15 g / L phytic acid, 30 mg / L sodium polydisulfide propane sulfonate, 20 mg / L sorbitol, 50 mg / L diethyl dithiophosphate ammonium salt, and the balance is deionized water.

[0081] Preparation Example 10

[0082] The gold plating solution includes the following components in mass concentration: 20 g / L sodium gold sulfite, 30 g / L malic acid, 20 g / L phytic acid, 40 mg / L sodium polydisulfide propane sulfonate, 30 mg / L sorbitol, 80 mg / L diethyl dithiophosphate ammonium salt, and the balance is deionized water.

[0083] Embodiment 1-3 provides a method for electroplating a molybdenum-copper material.

[0084] Example 1

[0085] A method for electroplating a molybdenum-copper material comprises the following steps:

[0086] S1. Soak the molybdenum-copper material in degreasing powder and wash for 30 minutes to remove excess material on the surface; wash the degreasing molybdenum-copper material with water, and then soak it in a 40wt% dilute hydrochloric acid solution for 30 seconds for pickling to remove surface oxides; wash the acidified molybdenum-copper material with water, and then soak it in a 20wt% dilute hydrochloric acid solution for 3 minutes for activation; wash the activated molybdenum-copper material with water to obtain a pretreated molybdenum-copper material;

[0087] S2. The pretreated molybdenum-copper material is first immersed in a nickel plating solution for bottom nickel plating. The external magnetic field is 0.3T, the temperature is 30°C, and the current density is 4A / dm 2 , the pulse frequency is 10Hz, the duty cycle is 20%, and the electroplating is 120s; then immersed in nickel flash liquid for nickel flash, and finally immersed in nickel plating liquid for nickel plating, the external magnetic field is 0.6T, the temperature is 40℃, and the current density is 1A / dm 2 , the pulse frequency is 10 Hz, the duty cycle is 30%, the electroplating is 300 s, and the nickel-molybdenum-copper plated material is obtained after washing;

[0088] Wherein, the nickel plating solution is prepared by Preparation Example 4; the nickel flash solution is prepared by Preparation Example 7;

[0089] S3, the nickel-molybdenum-copper plated material is immersed in the gold plating solution for gold plating, the external magnetic field is 0.6T, the temperature is 50℃, the pulse frequency is 10Hz, the duty cycle is 30%, and the current density is 50A / dm 2 , electroplating for 10 min, washing with water to obtain a gold-plated nickel-molybdenum-copper material;

[0090] Among them, the gold plating solution is prepared by Preparation Example 8.

[0091] Example 2

[0092] A method for electroplating a molybdenum-copper material comprises the following steps:

[0093] S1. Soak the molybdenum-copper material in degreasing powder and wash for 30 minutes to remove excess material on the surface; wash the degreasing molybdenum-copper material with water, and then soak it in a 40wt% dilute hydrochloric acid solution for 30 seconds for pickling to remove surface oxides; wash the acidified molybdenum-copper material with water, and then soak it in a 20wt% dilute hydrochloric acid solution for 3 minutes for activation; wash the activated molybdenum-copper material with water to obtain a pretreated molybdenum-copper material;

[0094] S2. The pretreated molybdenum-copper material is first immersed in a nickel plating solution for bottom nickel plating. The external magnetic field is 0.35T, the temperature is 35°C, and the current density is 6A / dm 2 , the pulse frequency is 10Hz, the duty cycle is 20%, and the electroplating is 135s; then immersed in nickel flash solution for nickel flash, and finally immersed in nickel plating solution for nickel plating, the external magnetic field is 0.7T, the temperature is 50℃, and the current density is 1.5A / dm2 , the pulse frequency is 10 Hz, the duty cycle is 30%, the electroplating time is 330 s, and the nickel-molybdenum-copper plated material is obtained after washing with water;

[0095] Wherein, the nickel plating solution is prepared by Preparation Example 5; the nickel flash solution is prepared by Preparation Example 7;

[0096] S3, the nickel-molybdenum-copper plated material is immersed in the gold plating solution for gold plating, the external magnetic field is 0.7T, the temperature is 50℃, the pulse frequency is 10Hz, the duty cycle is 30%, and the current density is 50A / dm 2 , electroplating for 10 min, washing with water to obtain a gold-plated nickel-molybdenum-copper material;

[0097] Among them, the gold plating solution is prepared by Preparation Example 9.

[0098] Example 3

[0099] A method for electroplating a molybdenum-copper material comprises the following steps:

[0100] S1. Soak the molybdenum-copper material in degreasing powder and wash for 30 minutes to remove excess material on the surface; wash the degreasing molybdenum-copper material with water, and then soak it in a 40wt% dilute hydrochloric acid solution for 30 seconds for pickling to remove surface oxides; wash the acidified molybdenum-copper material with water, and then soak it in a 20wt% dilute hydrochloric acid solution for 3 minutes for activation; wash the activated molybdenum-copper material with water to obtain a pretreated molybdenum-copper material;

[0101] S2. The pretreated molybdenum-copper material is first immersed in a nickel plating solution for bottom nickel plating. The external magnetic field is 0.4T, the temperature is 40°C, and the current density is 8A / dm 2 , the pulse frequency is 10Hz, the duty cycle is 20%, and the electroplating time is 150s; then immersed in nickel flash solution for nickel flash, and finally immersed in nickel plating solution for nickel plating, the external magnetic field is 0.8T, the temperature is 60℃, and the current density is 2A / dm 2 , the pulse frequency is 10 Hz, the duty cycle is 30%, the electroplating is 360 s, and the nickel-molybdenum-copper plated material is obtained after washing;

[0102] Wherein, the nickel plating solution is prepared by Preparation Example 6; the nickel flash solution is prepared by Preparation Example 7;

[0103] S3, the nickel-molybdenum-copper plated material is immersed in the gold plating solution for gold plating, the external magnetic field is 0.6-0.8T, the temperature is 50℃, the pulse frequency is 10Hz, the duty cycle is 30%, and the current density is 50A / dm 2 , electroplating for 10 min, washing with water to obtain a gold-plated nickel-molybdenum-copper material;

[0104] Among them, the gold plating solution is prepared by Preparation Example 10.

[0105] In order to verify the performance of the gold-plated nickel-molybdenum-copper material provided by the present application, the applicant set up comparative examples 1-6, in which:

[0106] Comparative Example 1

[0107] Comparative Example 1 is different from Example 1 only in that the nickel plating solution is prepared by Comparative Preparation Example 1.

[0108] Comparative Example 2

[0109] Comparative Example 2 is different from Example 1 only in that the nickel plating solution is prepared by Comparative Preparation Example 2.

[0110] Comparative Example 3

[0111] Comparative Example 3 is different from Example 1 only in that the nickel plating solution is prepared by Comparative Preparation Example 3.

[0112] Comparative Example 4

[0113] Comparative Example 4 is different from Example 1 only in that the nickel plating solution is prepared by Comparative Preparation Example 4.

[0114] Comparative Example 5

[0115] Comparative Example 5 is different from Example 1 only in that the nickel plating solution is prepared by Comparative Preparation Example 5.

[0116] Comparative Example 6

[0117] Comparative Example 6 is different from Example 1 only in that the nickel plating solution is prepared by Comparative Preparation Example 6.

[0118] The nickel-plated layer bonding strength, brazing verification and hardness of the nickel-plated molybdenum-copper materials obtained in step S2 of Examples 1-3 and Comparative Examples 1-6 were respectively tested, and the following result parameters were obtained, as shown in Table 1:

[0119] Coating bonding strength: Place the nickel-molybdenum-copper plated material in a 250°C oven and heat for 30 minutes. Take it out and immediately immerse it in water at room temperature. Take it out and dry it. Under an 8x magnification lighting observation system, check whether the coating has blistering and separation.

[0120] Brazing verification: AgCu28 solder, 4J50 frame and nickel-molybdenum-copper plated material are brazed at 890°C. After brazing, the appearance of the test piece after brazing is inspected in accordance with GJB923A-2004 "General Specification for Semiconductor Discrete Device Housing". The nickel plating layer shall not have blistering, copper corrosion, tearing and other problems;

[0121] Hardness: The Vickers hardness value of the nickel-plated layer of the nickel-molybdenum-copper plated material was measured using the HVS-1000 micro-Vickers hardness tester using the micro-Vickers hardness method.

[0122] Table 1:

[0123]

[0124]

[0125] It can be seen from the data shown in Table 1 above that the comprehensive performance of the gold-plated nickel-molybdenum-copper materials obtained in Examples 1-3 of the present application is far better than that of the gold-plated nickel-molybdenum-copper materials obtained in Comparative Examples 1-6. The nickel-plated layer has a greater hardness, and the bonding strength between the nickel-plated layer and the copper-molybdenum material surface is better. The surface is flat and smooth without bubbles.

[0126] It can be seen from Example 1 and Comparative Examples 1-3 that the nickel plating solution in Example 1 is prepared by Preparation Example 4, and the chitosan-based ionic liquid in Preparation Example 4 is prepared by Preparation Example 1. Compared with Comparative Examples 1-3, the nickel plating solution obtained in Preparation Example 4 has better stability, the coating of the nickel-molybdenum-copper material obtained in Example 1 does not bubble, and the coating does not tear after brazing.

[0127] It can be seen from Example 1 and Comparative Example 4 that the nickel plating solution in Example 1 is prepared by Preparation Example 4, and a low eutectic solvent is added to Preparation Example 4. Compared with Comparative Example 4, the comprehensive performance of the nickel-molybdenum-copper plated material obtained in Example 1 is greatly improved.

[0128] It can be seen from Example 1 and Comparative Examples 5 and 6 that the nickel plating solution in Example 1 is prepared by Preparation Example 4, and the brightener in Preparation Example 4 is obtained by mixing L-alanine benzyl p-toluenesulfonate and N-arylpyridine. Compared with Comparative Examples 5 and 6, the stability of the nickel plating solution obtained in Preparation Example 4 is better. The nickel-molybdenum-copper material obtained in Example 1 not only has significantly improved the brightness of the nickel plating layer, but also has strong bonding strength and is free of bubbles.

[0129] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for electroplating molybdenum-copper material, characterized in that: The following steps are involved: S1. The molybdenum-copper material is sequentially subjected to degreasing, water washing, oxidation, water washing, pickling, water washing, activation, and water washing treatment to obtain a pretreated molybdenum-copper material; S2, the pretreated molybdenum-copper material is first immersed in a nickel plating solution for bottom nickel plating, then immersed in a nickel flash solution for nickel flashing, and finally immersed in a nickel plating solution for nickel plating, washed with water, to obtain a nickel-plated molybdenum-copper material; S3, immersing the nickel-molybdenum-copper plated material in a gold plating solution for gold plating, and washing with water to obtain a gold-plated nickel-molybdenum-copper material; the nickel plating solution comprises the following components in mass concentration: nickel salt 80-110g / L, boric acid 40-50g / L, low eutectic solvent 50-150mg / L, chitosan-based ionic liquid 30-60mg / L, brightener 15-45mg / L, dispersant 40-80mg / L, defoamer 50-70mg / L, buffer 10-50mg / L, and the balance is deionized water.

2. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The nickel salt is at least one of nickel chloride, nickel sulfamate, nickel sulfate, nickel carbonate, nickel acetate, nickel formate, and nickel borofluoride.

3. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The low eutectic solvent is obtained by mixing salicylic acid, N,N-dimethylurea and distilled water in a molar ratio of 1:1:

2.

4. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The chitosan-based ionic liquid is prepared by the following method: Step A, add 1.32 g of N-methylbenzimidazole and 2-2.5 g of dibromopropane to 50 mL of acetone, react at 45-55° C. for 12-24 h, and then remove the solvent by rotary evaporation to obtain an intermediate; Step B: add 1.5 g of the intermediate and 0.01-0.05 g of potassium carbonate into 50 mL of distilled water, stir evenly, then add 1.0-1.8 g of chitosan and stir evenly, reflux at 110-120° C. for 18-24 h, cool, filter, wash with ethanol, and dry to obtain a chitosan-based ionic liquid.

5. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The brightener is obtained by mixing L-alanine benzyl ester p-toluenesulfonate and N-aryl pyridine in a mass ratio of 3-7:

10.

6. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The dispersant is at least one of polyethylene glycol, Tween, Span, lecithin and rhamnolipid; and the defoamer is an organosilicon defoamer.

7. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The buffer is a mixture of dipotassium hydrogen phosphate, malic acid and sodium gluconate in a mass ratio of 6:3:

1.

8. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The nickel flash solution includes the following components in mass concentration: 100 g / L nickel sulfate, 30 g / L potassium carbonate, 40 mg / L sodium alginate, 20 mg / L ethylene-acrylic acid copolymer, 10 mg / L carbazole, and the balance is deionized water.

9. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The gold plating solution comprises the following components in mass concentration: 10-20 g / L of sodium gold sulfite, 15-30 g / L of malic acid, 10-20 g / L of phytic acid, 10-40 mg / L of sodium polydisulfide propane sulfonate, 10-30 mg / L of sorbitol, 20-80 mg / L of diethyl dithiophosphate ammonium salt, and the balance is deionized water.

10. The electroplating method of a molybdenum-copper material according to claim 1, characterized in that: The parameters of the nickel plating in step S2 are: external magnetic field of 0.3-0.4T, temperature of 30-40°C, current density of 4-8A / dm 2 , the pulse frequency is 10Hz, the duty cycle is 20%, and the electroplating is 120-150s; the parameters of the nickel plating are: the external magnetic field is 0.6-0.8T, the temperature is 40-60℃, and the current density is 1-2A / dm 2 , the pulse frequency is 10Hz, the duty cycle is 30%, and the electroplating time is 300-360s.

Citation Information

Patent Citations

  • Method for electroplating surface of molybdenum and copper alloy

    CN102345145A

  • Preparation and application of imidazolium-based ionic liquid modified chitosan adsorbent

    CN106824113A

  • Novel method for electroplating gold on surface of molybdenum-copper alloy

    CN113445090A

  • Nickel-palladium-gold electroplating surface treatment process formula suitable for packaging substrate

    CN118326465A

  • Mono-fluid type metal NANO coating composition and preparation method of the same

    KR101271587B1